Pengaruh Latihan Permainan Target Terhadap Kemampuan Akurasi Smash Bola Voli Siswa di SMKN 2 Makassar - Akbar, Muh. Ainul; Hasmyati, Hasmyati; Juhanis, Juhanis; Hasan, Muh. Said; Hudain, Muh. Adnan (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to determine the effect of target game practice on the accuracy of students' smash ball at SMKN 2 Makassar. The sample in this study is 30 people. The research instruments used in this study include volleyball courts, volleyballs, nets and assessment sheets to record test results. The research method used is a pseudo-experimental research method, whichis research that compares the treatment group with the control group. Technically, the measurement of the results of the instrument was carried out on all samples through pretest andposttest, and then normality tests, homogeneity tests, and paired sample T-Test were carried out using the SPSS application. The results showed that the experimental group had a significance value of 0.000 and the control group 0.776. Based on the results of data analysis, the researcher concluded that there was a significant influence of the treatment group that was given target game training on the accuracy ability of smash ball by students at SMKN 2 Makassar and there was no significant influence of the control group that was not given target game practice on the accuracy ability of smash ball by students at SMKN 2 Makassar.